HUBUNGAN SCREEN TIME DENGAN KEMAMPUAN MOTORIK KASAR PADA ANAK USIA 2-3 TAHUN DI POSYANDU NAGARI SUNGAI PULAI - Anindhita Mella Pratama; Adnan Faris Naufal (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Background: With the rapid development of technology which is increasingly familiar to children's environments such as television, games, watching videos and opening social networks on mobile phones, it is a form of inactive behavior and if done with excessive time or often called with screentime it will make the child inactive so that it will hinder the development of gross motor skills in children. Purpose: To find out whether there is a relationship between screen time and gross motor skills in children aged 2-3 years in Nagari Sungai Pulai. Method: Using the Cross Sectional Study method, with a sample of 42 children using the Total Sampling technique. Results: Based on the results of research that has been conducted from the Spearman's rho test, a significant value of p=.000 is obtained which indicates a relationship between screen time and gross motor skills in children aged 2-3 years. The value of r = -.546 means that the level of closeness of the relationship is quite strong and the data is negative, that is, the value of the independent variable (screentime) increases, the value of the dependent variable (gross motor skills) decreases. Conclusion: Based on the results of research that has been done, it shows that there is a relationship between screen time and gross motor skills in children aged 2-3 years. A significance value of p=.000 or p<0.05 was obtained. The closeness level of the relationship is r = -.546, which is quite strong and the data is negative, that is, the value of the independent variable (screentime) increases, the value of the dependent variable (gross motor skills) decreases. Keywords: Screentime; Gross Motor; gadget